Assessing the cost-effectiveness of mepolizumab as add-on therapy to standard of care for severe eosinophilic asthma in Singapore. (2nd January 2022) - Tan, Ling Eng; Tan, Wan Hui Gloria; Aziz, Mohamed Ismail Abdul; Koh, Mariko Siyue; Tay, Tunn Ren; Pearce, Fiona; Ng, Kwong
Abstract: Objective: To evaluate the cost-effectiveness of mepolizumab added to standard of care (SOC) compared with SOC alone among patients with severe uncontrolled eosinophilic asthma in the Singapore setting. Methods: A Markov model with three health states (asthma on mepolizumab and SOC, asthma on SOC alone, and death) was developed from a healthcare system perspective over a lifetime horizon. During each 4-week cycle, patients in the non-death health states could experience asthma exacerbations requiring oral corticosteroid burst, emergency department visit, or hospitalization. Asthma-related mortality following an exacerbation or all-cause mortality could also occur at each cycle. The model was populated using local costs while utilities were derived from international literature. Transition probabilities were obtained from a mixture of Singapore-specific and internationally published data. Results: The base-case analysis comparing mepolizumab plus SOC with SOC alone resulted in an incremental cost-effectiveness ratio (ICER) of SGD335 486 (USD238 195) per quality-adjusted life-year (QALY) gained. Sensitivity analysis demonstrated that the ICER was most sensitive to the price of mepolizumab, followed by the proportion of exacerbations which required hospital intensive care. Despite restricting mepolizumab use to patients with a higher baseline exacerbation rate (3 in the past year) in a scenario analysis, the ICER remained high at SGD238 876 (USD 169 602) per QALY gained. Conclusion: At its current price, mepolizumab is not considered a cost-effective use of healthcare resources in Singapore. Substantial price reductions for mepolizumab are required to improve its cost-effectiveness to an acceptable range. These results will be useful to inform national funding decisions.